The role of financial media in share repurchases - A. Pinto-Gutiérrez, Cristian (Review of Business Management, 2016)
Purpose – This paper examines the impact that financial media coverage has on share repurchase outcomes in the U.S. Design/methodology/approach – I perform regression analysis to examine how the volume of firm-specific news articles about the announcements relates to firms’ decisions to actually repurchase shares following those announcements. I also examine the role of media in the firms’ long-term post-announcements stock performances. To alleviate concerns about confounding effects that can simultaneously drive both the volume of news articles and share repurchase outcomes, I use an instrumental variable approach. Findings – The results show that the levels of firm-specific media coverage at the time of repurchase announcements are negatively related to firms’ actual repurchases following the announcements. Furthermore, the evidence shows that twelve months following repurchase announcements, the highest cumulative abnormal returns correspond to the firms with the least media coverage. These results suggest that only those firms that do not attract sufficient investor attention to the announcements follow through on their repurchase programs. Originality/value – This paper augments the literature on behavioral finance by introducing and testing a firm-specific measure of investor attention by employing a newly available database of news articles from a news analytics provider. The paper also contributes to the sparse literature that examines the effects of investor attention on corporate events.